Repellent properties of celery, Apium graveolens L., compared with commercial repellents, against mosquitoes under laboratory and field conditions - Benjawan Tuetun (2018)
In our search for new bioactive products against mosquito vectors, we reported the slightly larvicidal and adulticidal potency, but remarkable repellency of Apium graveolens both in laboratory and field conditions. Repellency of the ethanolic preparation of hexane-extracted A. graveolens was, therefore, investigated and compared with those of 15 commercial mosquito repellents including the most widely used, DEET. Hexane-extracted A. graveolens showed a significant degree of repellency in a dose-dependent manner with vanillin added. Ethanolic A. graveolens formulations (10-25% with and without vanillin) provided 2-5 h protection against female Aedes aegypti. Repellency that derived from the most effective repellent, 25% of hexane-extracted A. graveolens with the addition of 5% vanillin, was comparable to the value obtained from 25% of DEET with 5% vanillin added. Moreover, commercial repellents, except formulations of DEET, showed lower repellency than that of A. graveolens extract. When applied on human skin under field conditions, the hexane-extracted A. graveolens plus 5% vanillin showed a strong repellent action against a wide range of mosquito species belonging to various genera. It had a protective effect against Aedes gardnerii, Aedes lineatopennis, Anopheles barbirostris, Armigeres subalbatus, Culex tritaeniorhynchus, Culex gelidus, Culex vishnui group and Mansonia uniformis. The hexane-extracted A. graveolens did not cause a burning sensation or dermal irritation when applied to human skin. No adverse effects were observed on the skin or other parts of the human volunteers' body during 6 months of the study period or in the following 3 months, after which time observations ceased. Therefore, A. graveolens can be a potential candidate for use in the development of commercial repellents that may be an alternative to conventional synthetic chemicals, particularly in community vector control applications. © 2005 Blackwell Publishing Ltd.